1998
DOI: 10.1021/bi9716579
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Fluorescence Quenching by Methionine and Selenomethionine Residues of Calmodulin:  Orientation of Peptide and Protein Binding

Abstract: The two interaction surfaces of the dumbbell-shaped calcium-regulatory protein calmodulin (CaM) are rich in the amino acid Met. In this work we have used fluorescence spectroscopy to study the role of these Met residues in binding the single Trp residue that is found in many CaM-binding domain peptides. This approach is facilitated by the absence of Trp residues in CaM. In addition to the wild-type protein, we studied CaM containing the unnatural amino acid selenomethionine (SeMet), which was biosynthetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
209
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 365 publications
(219 citation statements)
references
References 49 publications
10
209
0
Order By: Relevance
“…4)? Because selenomethionine can be biosynthetically incorporated into recombinant CaM (37), and because selenium can act as an efficient quencher of tryptophan fluorescence (31), we have previously taken advantage of these properties to determine the orientation of the complex between the myosin light chain kinase peptide and CaM by fluorescence spectroscopy (24). In agreement with NMR and x-ray studies (19,20), we have shown that the myosin light chain kinase peptide binds to CaM with topology A (see Fig.…”
Section: (Topology C) No Report Has Been Published That Describes a supporting
confidence: 59%
See 4 more Smart Citations
“…4)? Because selenomethionine can be biosynthetically incorporated into recombinant CaM (37), and because selenium can act as an efficient quencher of tryptophan fluorescence (31), we have previously taken advantage of these properties to determine the orientation of the complex between the myosin light chain kinase peptide and CaM by fluorescence spectroscopy (24). In agreement with NMR and x-ray studies (19,20), we have shown that the myosin light chain kinase peptide binds to CaM with topology A (see Fig.…”
Section: (Topology C) No Report Has Been Published That Describes a supporting
confidence: 59%
“…On the basis of these results, we propose that the effector domain of MRP is associated with CaM in an orientation that is similar to myosin light chain kinase (19,20,24) and CaM kinase I (24) (topology A in Fig. 4).…”
Section: (Topology C) No Report Has Been Published That Describes a mentioning
confidence: 85%
See 3 more Smart Citations